How al-Andalus wrapped itself in a silk cocoon: the ṭirāz between Umayyad economic policy and Mediterranean trade. - Lopez-Marigorta, Eneko (Mediterranean Historical Review, 2023)
Sericulture and the state supervision of textile production was a longstanding tradition in the Middle East during the pre-Islamic period. However, neither were known in the Iberian Peninsula. With the rise of Islam, the luxury fabrics produced by the state institution of ṭirāz became a prominent symbol of sovereignty, encouraging the Umayyads of al-Andalus (138 h./756–422 h./1031) to create their own ṭirāz workshop, which specialized in silk fabrics, after sericulture was introduced in Iberia under their rule. Little was known about this productive process, as existing studies have tended to focus exclusively on one of the multiple types of evidence available: Arabic, Latin and Hebrew textual sources; chemical, technical and decorative analysis of preserved textiles; and others. This paper uses all the evidence available to undertake a comprehensive study of the operation of the Umayyad ṭirāz workshop in al-Andalus. Beginning with the tributary and administrative factors that surrounded the institution, the process by which demand for silk in the Mediterranean markets gave private merchants the instruments to control the Andalusi textile sector is analysed. By the fifth h./eleventh century, al-Andalus had become the main supplier of silk goods in the Mediterranean.